A round of robins - Hesterman, Katie; Ruzzier, Sergio, 1966- (New York, NY : Nancy Paulsen Books, 2018)
"Follow a pair of robin parents from nest-building and egg-laying, to raising their hungry hatchlings, and finally sending off their flying fledglings"--
Keywords: Stories in rhyme; Robins -- Life cycles -- Juvenile fiction; Birds -- Nests -- Juvenile fiction; Stories in rhyme; Robins -- Fiction; Birds -- Nests -- Fiction; JUVENILE FICTION -- Animals -- Birds; JUVENILE FICTION -- Family -- General (see also headings under Social Issues); JUVENILE FICTION -- Stories in Verse; Birds -- Nests; Robins -- Life cycles; Robins -- Fiction; Birds -- Nests -- Fiction; Stories in rhyme; Picture books; Juvenile works; Fiction; Stories in rhyme; Picture books; Stories in rhyme